2020
DOI: 10.5664/jcsm.8494
|View full text |Cite
|
Sign up to set email alerts
|

Association between weekend catch-up sleep and executive functions in Chinese school-aged children

Abstract: Study Objectives: Although weekend catch-up sleep is common among children, the association between weekend catch-up sleep and executive functions remains unclear. We aimed to determine whether weekend catch-up sleep was related to executive functions in school-aged children. Methods: We analyzed data for 4,699 children (9.00 years ± 1.73 years old, 52.9% boys) from 5 primary schools in Guangzhou, China. Executive functions performance was examined by the Behavior Rating Inventory of Executive Function Parent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 43 publications
3
16
0
Order By: Relevance
“…Indeed, the heterogeneity in the within-person relations between sleep and EF implied that one model did not fit all participants. Such a finding might be a reason why there is inconsistency in findings of the relations between sleep and EF using between-person approaches or average within-person effects (e.g., Anderson et al, 2009;Lv et al, 2020). The heterogeneity in the sleep-EF coaction is consistent with ideas derived from the RDS metatheory.…”
Section: Moving From the Average Effect To Person-specific Effectssupporting
confidence: 66%
See 1 more Smart Citation
“…Indeed, the heterogeneity in the within-person relations between sleep and EF implied that one model did not fit all participants. Such a finding might be a reason why there is inconsistency in findings of the relations between sleep and EF using between-person approaches or average within-person effects (e.g., Anderson et al, 2009;Lv et al, 2020). The heterogeneity in the sleep-EF coaction is consistent with ideas derived from the RDS metatheory.…”
Section: Moving From the Average Effect To Person-specific Effectssupporting
confidence: 66%
“…Although most of this literature suggests that sleep is important for EF, not all group-based and average-focused studies of sleep and EF support this conclusion (for reviews, see Chaput et al, 2016;Reynaud et al, 2018). Some crosssectional studies based on self-report data from adolescents find that sleep duration was not significantly associated with EF (Anderson et al, 2009) and at least one study has reported a negative association between sleep duration and EF (Lv et al, 2020). Some experimental studies also find that adolescents who are assigned to sleep restriction conditions do not perform worse in EF tasks than those in non-restriction conditions (Beebe et al, 2019;Suppiah et al, 2016;Voderholzer et al, 2011).…”
Section: Person-specificity In Relations Between Executive Functionin...mentioning
confidence: 99%
“…Difference, similar to jet lag between sleep pattern on weekends and school days are known as "social jet lag" 8, 9 . In children and adolescents, it is common that weekend sleep patterns are not as same as the study days 10,11 . Objective measurements of sleep and light collected every 6 months for 14 days in Australian children aged 10 to 15 years revealed that non-myopic children had more regular sleep status (seldom staying up late and putting off getting up), while myopic children showed greater variability, whether it was the study day or weekend, summer or winter 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have found that WCUS is associated with a lower risk of hypertension [11], obesity prevention in adults [14], and lower frequency of asthma in adolescents [3]. In contrast, WCUS had adverse effects on executive functions, 15 and contributes to suicidal attempts and self-injury in children and adolescents [16].…”
Section: Introductionmentioning
confidence: 99%